Experimental Study on Fresh and Hardened Properties of Concrete with Fine Aggregate Replacement by Manufactured Sand - Pooja Raj; Dharmendra Prajapati (International Journal of Scientific Research in Civil Engineering, 2025)
The growing demand for natural river sand as a fine aggregate in concrete production has led to over-exploitation of riverbeds, causing environmental concerns such as soil erosion and depletion of aquatic ecosystems. Consequently, there has been a significant shift toward finding sustainable alternatives to natural sand. One such alternative is Manufactured Sand (M-sand), which is produced by crushing granite stone and can serve as a viable replacement for river sand in concrete. This study explores the potential of M-sand as a substitute for natural river sand in the production of M40 grade concrete. The primary objective of this research is to evaluate the impact of different proportions of M-sand on the mechanical and durability properties of concrete. In this study, M-sand was used as a partial replacement for river sand in varying proportions, ranging from 0% to 100% in increments of 10%. The mix design was based on the IS: 10262 – 1982 standard, and various concrete tests were performed to assess its workability, compressive strength, splitting tensile strength, flexural strength, and water absorption. Ordinary Portland Cement (OPC) 53-grade was used in the mix along with crushed granite as coarse aggregates. The study included an investigation of the effect of M-sand on the workability of fresh concrete and the mechanical strength of hardened concrete, including compressive, tensile, and flexural strength, to understand the structural performance of the concrete.
Keywords: Manufactured Sand (M-sand); River Sand; Concrete; M40 Grade Concrete; Mechanical Properties; Durability; Compressive Strength; Tensile Strength; Flexural Strength; Workability